ETNOPEDAGOGI: PERSEPSI DAN IMPLEMENTASINYA DI SEKOLAH DASAR - Rahayu, Galih Dani Septiyan; Rahman, Rahman; Karlina, Dety Amelia; Anggraini, Gian Fitria; Ratumanan, Stelie D (P2M STKIP Siliwangi, 2021)
The transformation of culture to the younger generation is very important to be carried out through learning in schools by integrating culture and cultural values in the ethno-pedagogical-based learning process. Based on this statement, the purpose of this study was to analyze school teachers' perceptions of Ethno pedagogy and its implementation in learning in elementary schools. The method used in this research is the descriptive method with survey design. The subjects in this study were elementary school teachers in one of the cities in West Java with a total of 89 teachers. The research instrument is an interview sheet instrument to determine the perception of elementary school teachers on Ethno pedagogy and its implementation. The results of his research obtained several themes regarding Ethno pedagogy, namely learning based on local wisdom values, culture-based learning, and learning based on ethnic diversity, ethnicity, and customs, 81% of 89 elementary school teachers had implemented Ethno pedagogy-based learning, and 100% of 89 teachers stated that Ethno pedagogy is very important to understand and implement in learning in elementary schools.Â